2021
DOI: 10.24198/adbispreneur.v5i3.29953
|View full text |Cite
|
Sign up to set email alerts
|

Work Engagement Karyawan Generasi Milenial Pada Pt. X Bandung

Abstract: This article aims to determine the description and level of work engagement of millennial generation employees at PT X. The method used is a quantitative method with a descriptive approach. The study population was all employees of the millennial generation of PT. X total 132 employees. The sampling technique used the Slovin formula with a total of 57 people. Collecting data in the form of a work engagement questionnaire with dimensions of vigor, dedication and absorption, interviews, and observation. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Karyawan generasi milenial dapat memiliki penghayatan yang baik dalam pekerjaan karena memiliki kebebasan untuk memutuskan tanggung jawab mereka sendiri dan memiliki variasi pekerjaan yang beragam, identitas tugas juga dapat membuat karyawan dapat berkonsentrasi penuh dalam pekerjaannya karena identitas tugas karyawan yang diberikan kebebasan dalam melakukan pekerjaan dapat berkonsentrasi penuh dalam melakukan pekerjaannya (Dewi et al, 2021). Umpan balik dapat membantu karyawan apabila dihadapkan dengan tugas yang kurang dikuasai, karyawan akan berdiskusi dengan rekan kerja atau atasannya untuk mencari solusi dari permasalahannya (Sukoco et al, 2021).…”
Section: Pembahasanunclassified
“…Karyawan generasi milenial dapat memiliki penghayatan yang baik dalam pekerjaan karena memiliki kebebasan untuk memutuskan tanggung jawab mereka sendiri dan memiliki variasi pekerjaan yang beragam, identitas tugas juga dapat membuat karyawan dapat berkonsentrasi penuh dalam pekerjaannya karena identitas tugas karyawan yang diberikan kebebasan dalam melakukan pekerjaan dapat berkonsentrasi penuh dalam melakukan pekerjaannya (Dewi et al, 2021). Umpan balik dapat membantu karyawan apabila dihadapkan dengan tugas yang kurang dikuasai, karyawan akan berdiskusi dengan rekan kerja atau atasannya untuk mencari solusi dari permasalahannya (Sukoco et al, 2021).…”
Section: Pembahasanunclassified
“…Engagement can be understood as behavior that produces positive situations and high motivation, thereby creating dedication and good focus by employees on the work they do (Bakker & Albrecht, 2018). According to Sukoco et al (2021), work engagement is shown by the outcome of employees who have focus and concentration in the high category, even though the work they have is classified as difficult. Positive things implemented by employees with high work engagement will be able to increase the company's success.…”
Section: Introductionmentioning
confidence: 99%
“…In the opinion of Takawira et al, 2014 the challenges of the organization today are not only retaining superior employees but also focusing on making employees feel attached to the organization/company so that they are skilled and fully involved in the work. Work engagement is very important for employees because it can have a positive impact on both employees and the company financially and organizationally (Sukoco et al, 2020). However, the reality is that currently according to Wicaksono, in 2020 only 36% of millennial workers in Indonesia feel attached to their company.…”
mentioning
confidence: 99%